Flux vs. permeability: How to effectively evaluate mass transfer performance of membranes in oil-water separation. (October 2022) - Ni, Tianlong; Kong, Lingxue; Xie, Zongli; Lin, Jiuyang; Zhao, Shuaifei
Abstract: Membrane filtration has attracted surging attention for various water treatment applications, such as oil-water separation, because of its low energy consumption, high separation efficiency, and wide applicability for various feed solutions. The advances of fabricated membranes are often emphasized by high permeation flux and separation efficiency. However, as "membrane-independent factors" (e.g. filtration areas and pressures) also contribute to the variation of mass transfer during the separation, the comparison based on the flux from batch experiments leads to a pitfall in evaluating the membrane performance. Our water permeation experiments using different set-ups demonstrate that the permeability result are more reliable and comparable than the flux value for evaluating membrane permeation performance since it considers the driving force from either hydraulic pressure or external pressure. However, flux and permeability may vary significantly among different studies, depending on the selection of the measurement period during the filtration experiment. To effectively evaluate the mass transfer performance, we recommend using the permeability profile with a constant driving force. The permeability profile under a constant driving force is a desirable way to evaluate the membrane performance, as it can describe both the mass transfer performance and the antifouling performance of a membrane. These key conclusions are drawn from oil-water separation membranes but also applicable for other pressure-driven separation membranes. This study provides a guideline for effective membrane performance evaluation by demonstrating improved experimental and data analysis methods. Graphical abstract: Unlabelled Image Highlights: We compared with the flux and permeability for membrane performance evaluation. Flux may lead to a pitfall in evaluating membrane mass transfer performance. Permeability is more reliable and comparable in evaluating membrane performance. Permeability profile is recommended to evaluate membrane performance. This study provides a guideline for effective membrane performance evaluation.